Scientific Approaches to Brand Evaluation Methodology and It`s Problems - kramovich, Ikramov Murat (International Journal of Psychosocial Rehabilitation, 2020)
In Uzbekistan, enterprises operate in conditions when rapid development and changes in markets are taking place, and competition with foreign firms with many years of experience is intensifying. This greatly increases the need for the development, adaptation and application of advanced technologies and management methods, one of which is branding. The transition to an innovative economy of a modern industrial enterprise requires a radical reform of the brand management mechanisms, as well as the creation of support measures both on the part of the state and on the enterprise itself when developing and mastering innovative branding solutions. The article deals with the operational determination of the effectiveness of the company as a whole, as clarification of its place in the industry and the regional economy, as well as the main methods for evaluating trademarks.